Aplikasi Jenis Pupuk organik terhadap Kadar Hara NPK dan Produksi Kedelai (Glycine max (L.) Merril) pada Jarak Tanam yang Berbeda di Lahan Pasang Surut - Neni Marlina; Iin Siti Aminah; Nurbaiti Amir; Rosmiah Rosmiah (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2019)
Marlina N, Aminah IS, Amir N, Rosmiah R. 2019. Application of organic fertilizer types to NPK nutrients levels and soybeans production (Glycine max (L.) Merril) at different planting spaces in tidal land. Jurnal Lahan Suboptimal: Journal of Suboptimal Lands. 8(2):148-158.  Tidal lowlands flood type C is suboptimal land and very potential in cultivating soybean, but it has problems in soil fertility, macro and micro nutrient poor, therefore to increase soil fertility can be given various types of organic fertilizers, including cow manure organic fertilizer, chicken manure organic fertilizer and biofertilizer. All types of organic fertilizers are composted, and specifically biofertilizers are made with their own formula. It is expected that the organic fertilizer provided can increase soil fertility and nutrient availability for soybean plants. This study aimed to get the best type of organic fertilizer on the availability of nutrient levels of NPK and soybean production at different spacing in tidal land.  This research was conducted in Jaya Agung Village, Lalan District, Musi Banyuasin Regency, South Sumatra Province, and was carried out in March 2018 - June 2018. The method used was the experimental method. The design used is a split-plot design. with 9 treatment combinations and repeated 3 times. As the main plot treatment is plant spacing (20 cm x 20 cm, 20 cm x 30 cm and 20 cm x 40 cm), and treatment of subplots are: types of cow manure organic fertilizers  10 ton/ha, chicken manure organic fertilizer 10 ton/ha, and biofertilizer 400 kg/ha. The results showed that the combination treatment of plant spacing of 20 cm x 30 cm with the type of biofertilizer 400 kg/ha could  increase   soybean production by 9.11 g/plot or equivalent to 2.43 ton/ha.